Histomorphological Spectrum of Bone Tumors in A Tertiary Care Hospital - Kaur, Ashmeet; Faujdar, Mansi; Nakra, Sohil; Gupta, Shubha (Annals of Pathology and Laboratory Medicine, 2018)
Background: Bone tumors are relatively uncommon, constituting only 0.5% of all types of cancer. Many bone tumor entities show a remarkable consistency in clinical presentation, age and anatomic site distribution. The final diagnosis of bone tumors should be based on an integrated use of histopathologic findings, clinical presentation, and imaging characteristics. Immunohistochemical and genetic/molecular techniques are at times crucial for the definite classification of certain bone tumors. Objective: The aim of the present study was to determine the spectrum, frequency and demographics of bone tumors at our institute Santokba Durlabhji Memorial Hospital, Jaipur. Materials and Method: A retrospective review of histopathological reports of all bone specimens received in the department of pathology (histopathology section) for a period of 3 years from January 2014 to January 2017 Results: On histopathological diagnosis, among neoplastic lesions incidence of benign tumors was 447 cases (60.4%), and malignant tumors was 293cases (39.6 %). Among the benign tumors, the most common benign tumor was Giant cell tumor 99 cases (13.3%). Osteosarcoma was commonest malignant tumor 42 cases (5.6%). Maximum number of bone tumors occurred in 15-45 years of age and the male to female ratio was 2:1 Conclusions: Bone tumors occurred predominantly within 15-45 years of age with a male preponderance. Giant cell tumor was the most common benign tumor, while Osteosarcoma was the most common malignant bone tumor. Femur is the most common site for bone tumors.